Extracellular HMGB-1 activates inflammatory signaling in tendon cells and tissues - Chuanxin Zhang; Xinfeng Gu; Guangyi Zhao; Wang Wang; Jiahua Shao; Jun Zhu; Ting Yuan; Jiuyi Sun; Daibang Nie; Yiqin Zhou (SAGE Publishing, 2020)
Background: Increasing evidence indicates that secretion of high mobility group box 1 protein (HMGB-1) is functionally associated with tendinopathy development. However, the underlying effect and mechanism of extracellular HMGB-1 on tendon cells are unclear. Methods: We tested the effect of exogenous HMGB-1 on cell growth, migration, and inflammatory signaling responses with isolated rat Achilles tendon cells. Also, we studied the role of extracellular HMGB-1, when administrated alone or in combination with mechanical overloading induced by intensive treadmill running (ITR), in stimulating inflammatory effects in tendon tissues. Results: By using in vitro and in vivo models, we show for the first time that exogenous HMGB-1 dose-dependently induces inflammatory reactions in tendon cells and tendon tissue. Extracellular HMGB-1 promoted redistribution of HMGB-1 from the nucleus to the cytoplasm, and activated canonical nuclear factor kappa B (NF-κB) signaling and mitogen-activated protein kinase (MAPK) signaling. Short-term administration of HMGB-1 induced hyper-cellularity of rat Achilles tendon tissues, accompanied with enhanced immune cell infiltration. Additional ITR to HMGB-1 treatment worsens these responses, and application of HMGB-1 specific inhibitor glycyrrhizin (GL) completely abolishes such inflammatory effects in tendon tissues. Conclusion: Collectively, these results confirm that HMGB-1 plays key roles in the induction of tendinopathy. Our findings improve the understanding of the molecular and cellular mechanisms during tendinopathy development, and provide essential information for potential targeted treatments of tendinopathy.